The American Origin of the French Revolution - Sebastian Ottinger; Lukas Rosenberger (Institute of Labor Economics (IZA), 2023)
France sent five thousand men to fight alongside George Washington's army in the American Revolutionary War. We show that the French combatants' exposure to the United States of America increased support for the French Revolution a decade later. French regions (départements) from which more American combatants originated had more revolutionary societies, volunteers for the revolutionary army, riots against feudal institutions, and emigrants from the Old Regime's elite. To establish causality, we exploit two historical coincidences: i) originally, a French army of seven and a half thousand was ready to board ships but one third did not sail to America because of logistical problems; ii) among the regiments who fought in America against the British, some regiments were stationed for one year in New England before the main battle, and in Virginia afterwards, while others were stationed in the Caribbean colonies. We find that only the combatants who were exposed to the United States affected the French Revolution after their return.
Keywords: N4; D74; H1; 330; institutional change; French Revolution; American War of Independence